Simulations and experimental validation of one cycle controlled nine-level inverter using FPGA. (December 2020) - Ul-Haq, Azhar; Jalal, Marium; Aamir, Muhammad; Cecati, Carlo; Muslim, Fahad Bin; Raja, Arsalan Ahmad; Iqbal, Javed
Abstract: This paper presents an extensive simulation-based and experimental validation of One-Cycle Control (OCC) over a nine-level power inverter using Cyclone III FPGA from Intel. OCC is a technique that exploits the nonlinear nature of multilevel power converters to overcome issues such as fast dynamic response, robustness and perturbations on either the source or the load side. Simulations performed in Modelsim demonstrate the elimination of dynamic and steady-state error between the switched output and reference signals on application of OCC. Simulink-based development and testing of the multilevel inverter model is also carried out under varying load conditions to record the reference signal, current, power factor and total harmonic distortion. The applied control scheme exhibits negligible current distortion and instability concerns when the converter is lightly loaded. Altera Quarturs II is further used for the VHDL-based implementation and experimental testing of the developed algorithm thus, validating the robustness of the control strategy.